ASGBOOKSYS: All Star Gym Booking System with Usability Heuristic Theory Adaptation - Ibrahim, Normalina; Fauzee, Farisa Aqilla; Sa’dan, Siti ‘Aisyah; Mohd Bahrin, Ummu Fatihah (Journal of Information Systems Research and Practice, 2024)
All Star Gym Booking System (ASGBookSys) is a system that is made for All Star Gym that is located at Kuala Terengganu, Terengganu. This system’s main objective is to simplify the process of handling gym bookings. Initially, customers had difficulty booking the gym because there was no automated system to handle the booking. Customers must contact the gym’s staff before making a booking to find out the available date and time. The staff also has difficulties keeping and tracking information about customer bookings in the logbook. Because there is no automated system in place, the system administrator, who is also the gym’s owner, finds it challenging to monitor the gym process. The existence of ASGBookSys enables the resolution of all identified issues, including the system’s ability to verify availability prior to customer booking, store data in an unlimited system database, and establish user-level data access restrictions. The booking process is easier and faster for the customers. ASGBookSys was developed using the Adapted Waterfall Model, where four stages were included which are requirement analysis, design, implementation, and testing. The project also employs the Ten Usability Heuristics as its theoretical framework. It has served as the guideline for developing this system. The system has passed all the requirements in the test plan. We used expert and usability evaluations to assess the system, considering all feedback. The evaluation reveals that the system interface is the cornerstone of system usability, boasting a mean score of 4.57. In the future, some enhancements will be made to improve the ASGBookSys such as online payment after booking confirmation.